CHRONIC COLITIS ALTERS BRAIN ACTIVITY BY INDUCING HMGB1-MEDIATED PYROPTOSIS IN MICE. (22nd January 2022) - Mitchell, Jonathon; Kim, Su Jin; Howe, Cody; Patel, Marisa; Kim, Gayoung; Heo, Gwangbeom; Im, Eunok; Rhee, Sang
Abstract: BACKGROUND AND AIM: Chronic gut inflammation such as inflammatory bowel diseases is thought as being associated with neurodegenerative diseases in humans. The direct evidence for and the underlying mechanism of this brain-gut interaction, however, remain elusive. METHODS: We used manganese-enhanced magnetic resonance imaging (MEMRI) to assess brain functional activity from awake and freely moving mice. As a mouse model of chronic colitis, mice were treated with three cycles of dextran sulfate sodium. We performed the passive avoidance test, which is a fear-motivated test that assesses short-term and long-term memory. Mouse hippocampus tissues and microglial cells were subjected to GC-MS, immunofluorescence staining, ELISA, and immunoblotting analysis to examine how the inflamed gut is linked to the brain pathology. RESULTS: We found that manganese ion uptake, indicative of Ca 2+ influx into neuronal cells, and accumulation are dramatically reduced in the hippocampus of chronic colitis mice compared to control mice. Long-term memory is declined in chronic colitis mice. Neuroinflammatory signals, including IL-1β production and the activation of Caspase-1, Caspase-11, and Gasdermin (GSDM), are induced in the hippocampus of chronic colitis mice. High-mobility group box 1 (HMGB1) level is elevated both in the serum and in the hippocampus of chronic colitis mice; however, lipopolysaccharide (LPS) levels remain at low levels without significant changes in these samples. The blood-brain barrier permeability is increased in chronic colitis mice. In the presence of LPS, accordingly, HMGB1 treatment induces the activation of Caspase-11 and GSDM in mouse microglial cell line SIM-A9. CONCLUSION: Our findings suggest that HMGB1 released from the inflamed intestine may move to the brain through the blood circulatory system; in conjunction with a low level of endogenous LPS, elevated HMGB1 can subsequently activate Caspase-mediated inflammatory responses in the brain. This study implies that chronic gut inflammation may alter brain activity in mice.